GM-016 Budget Impact Analysis of a protocol for selection of biological treatment in rheumatoid arthritis. (24th February 2014) - Navarro, H; Manero, J; Escolano, A; Huarte, R; Larrodé, I; Abad, MR
Abstract : Background: Our Community Public Health System established a protocol for biological treatment of rheumatoid arthritis in May 2011. Purpose: To perform a Budget Impact Analysis folowing the introduction of a protocol for biological treatment (BT) in rheumatoid arthritis (RA). Materials and methods: Patients with AR treated with BT and the associated cost were analysed, before and after protocol implementation (second semester of 2010, 2011 and 2012). Protocol levels: 1 st line: infliximab or a subcutaneous tumour necrosis factor inhibitor (etanercept or adalimumab), considering the evidence for the same effectiveness and safety; 2 nd line: tocilizumab or abatacept or rituximab; 3rd line: golimumab or certolizumab. After negotiations with manufacturers, our health system decided to start treatment with etanercept as the less expensive TNF inhibitor. Collected data: number of patients per drug, average cost/patient in a semester and compliance rate according to European public assessment reports (EPAR) posology. The cost/patient indicator was calculated by adjusting treatment time to six months. Results: RA patients account for 48% of patients with rheumatic diseases treated with TB. The number of RA patients treated rose over the three periods studied, 179 patients in 2010, 211 in 2011 and 236 in 2012; etanercept use increased from 35% to 40%. Average cost in AR patients was: 5, 620 € in 2010 second semester, 5, 458 € in the same period of 2011 and 5, 252 € in 2012. The number of patients increased by 32% from 2010 to 2012, but the cost rose by only 23%. The etanercept compliance rates according to EPAR posology were 92%, 89% and 89% in 2010, 2011 and 2012 respectively. Conclusions: Implementation of a protocol and dose optimisation allowed savings of 700 € per patient/year comparing 2012 and 2010. The establishment of a protocol prioritises the use of lower-priced drugs and enables centralised negotiating. The goal of efficiency is to optimise the cost opportunity: more patients treated with less impact on the budget. No conflict of interest.